Spontaneous Spinal Epidural Hematoma With Hemiparesis Masquerading as Acute Cerebral Infarction: A Case Report. Issue 3 (August 2016) - Kim, Chong Myung; Park, Jung-Soo; Lee, Jong-Myong; Koh, Eun-Jeong
Abstract : Acute onset hemiparesis is a common initial presentation of cerebral ischemic stroke. However, other possibilities should be considered as well before final diagnosis. Motor deficits resulting from spontaneous spinal epidural hematoma (SSEH) are usually paraparesis or quadriparesis, but a few cases of SSEH that presented hemiparesis have been documented and misdiagnosed as cerebral ischemic stroke. Herein, we present a rare case of SSEH with acute hemiparesis, which was initially misdiagnosed.